A Systematic Literature Review of Employee Performance Appraisal Decision Support System - Ery Oktavianingrum; Ifah Rofiqoh (Edunity Kajian Ilmu Sosial dan Pendidikan, 2025)
Employees in an agency or company are the most important assets that affect the progress of a company, so there is a need to improve the quality of employee performance. Employee performance is an achievement achieved by an employee in carrying out work in accordance with the standards or criteria set in the company.  The need for employee performance is important in an agency or company because it is related to a decision-making system for the company. This study aims to analyze the practice of decision-making systems for employee performance assessment. The method used in writing this article is literature review. The results of the study show that important indicators or criteria are considered in determining the weight of employee assessments. The methods of a Decision Making System (SPK) are very diverse to support the ranking and determinants of employee assessment decisions. Based on the literature review above, the author argues that the decision support system in assessing the best employee performance is with the Simple Additive Weighting (SAW) algorithm. This is supported by the assessment criteria used, including work performance, loyalty, initiative, responsibility, cooperation, communication, discipline, obedience and leadership. These criteria are often used in research to assess employee performance and produce a decision related to human resources that can be used by leaders in determining their company goals.